2019
DOI: 10.1002/glia.23769
|View full text |Cite
|
Sign up to set email alerts
|

Gpr126/Adgrg6 contributes to the terminal Schwann cell response at the neuromuscular junction following peripheral nerve injury

Abstract: Gpr126/Adgrg6 is an adhesion G protein‐coupled receptor essential for Schwann cell (SC) myelination with important contributions to repair after nerve crush injury. Despite critical functions in myelinating SCs, the role of Gpr126 within nonmyelinating terminal Schwann cells (tSCs) at the neuromuscular junction (NMJ), is not known. tSCs have important functions in synaptic maintenance and reinnervation, and after injury tSCs extend cytoplasmic processes to guide regenerating axons to the denervated NMJ. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 69 publications
(97 reference statements)
0
37
0
Order By: Relevance
“…In addition, Adgrg6 is involved in the remyelination of axons (Mogha et al, 2016) and reinnervation of neuromuscular junctions (Jablonka-Shariff et al, 2020) after nerve injury. Whereas the inducible knockout of Adgrg6 in Schwann cells did not result in signs of demyelination for up to 4 months (Mogha et al, 2016), aged conditional Adgrg6 knockout mice showed neuromuscular junction alterations and signs of denervation in hindlimbs, consistent with chronic disruption of Schwann cell function (Jablonka-Shariff et al, 2020). Together with the 5 late-onset demyelinating neuropathy of PrP knockout mice, these findings suggest that Adgrg6 is not only required for the initiation of myelination, but also for long-term myelin maintenance.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, Adgrg6 is involved in the remyelination of axons (Mogha et al, 2016) and reinnervation of neuromuscular junctions (Jablonka-Shariff et al, 2020) after nerve injury. Whereas the inducible knockout of Adgrg6 in Schwann cells did not result in signs of demyelination for up to 4 months (Mogha et al, 2016), aged conditional Adgrg6 knockout mice showed neuromuscular junction alterations and signs of denervation in hindlimbs, consistent with chronic disruption of Schwann cell function (Jablonka-Shariff et al, 2020). Together with the 5 late-onset demyelinating neuropathy of PrP knockout mice, these findings suggest that Adgrg6 is not only required for the initiation of myelination, but also for long-term myelin maintenance.…”
Section: Introductionmentioning
confidence: 80%
“…Adgrg6 is expressed in Schwann cells and was shown to have autonomous and nonautonomous functions in peripheral nerve repair (4,5). PrP is an agonist of Adgrg6 on Schwann cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…The reciprocal interaction between axons, Schwann cells and the extracellular matrix is crucial for development, maintenance and repair of the peripheral nervous system (PNS) (1,2). The adhesion G-protein coupled receptor Adgrg6 (formerly called Gpr126) was shown to be required for Schwann cell development (3), peripheral nerve repair (4,5) and possibly myelin maintenance (4). Three natural ligands for Adgrg6 have been described: collagen IV (6), laminin-211 (7) and the prion protein (PrP) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Later, a contribution of Adgrg6 to macrophage recruitment and remyelination after nerve crush injury was demonstrated [ 12 ], indicating that Adgrg6 is also involved in PNS repair. Furthermore, Adgrg6 is required for responses of terminal Schwann cells and regeneration of neuromuscular junctions [ 13 ], which is crucial for the restoration of function after peripheral nerve injury. Finally, ageing conditional Adgrg6 knockout mice showed signs of hindlimb denervation [ 13 ], suggesting a role of Adgrg6 signaling in maintenance of peripheral myelin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Adgrg6 is required for responses of terminal Schwann cells and regeneration of neuromuscular junctions [ 13 ], which is crucial for the restoration of function after peripheral nerve injury. Finally, ageing conditional Adgrg6 knockout mice showed signs of hindlimb denervation [ 13 ], suggesting a role of Adgrg6 signaling in maintenance of peripheral myelin. This notion is supported by the development of a progressive demyelinating neuropathy of the PNS in mice devoid of the cellular prion protein (PrP), an agonist of Adgrg6 [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%